Can incomplete information lead to better social outcomes?. (24th January 2020) - Lahkar, Ratul; Ramani, Vinay
Abstract : We consider a supply chain where manufacturers can be differentiated along two dimensions—product quality and cost of social responsibility effort. There are two types of manufacturers: high and low. Under complete information, high‐type manufacturers exert a greater level of social responsibility effort in comparison with the low‐type manufacturers. We then show that under incomplete information, high‐type manufacturers have an incentive to exert an even greater level of social responsibility effort. Surprisingly, the extent of effort put in by high‐type firms cannot be lower and, in some cases, can be strictly higher under incomplete information.